Analisis Pengaruh Pembiayaan Mudharabah dan Pembiayaan Musyarakah Terhadap Rasio Profitabilitas (ROE) Return On Equity - Andika Yanuar Ramadani; Wirman Wirman (Peneliti.net, 2023)
The research this study aims to find out and analyze how the influence of mudharabah financing and musyarakah financing on the level of profitability at PT Bank Muamalat Indonesia, Tbk with the variable studied is Return On Equity. This study uses monthly financial report data taken in the 2018-2021 period published on www.ojk.go.id. The independent variable (X) used in this study includes: mudharabah financing and musyarakah financing. The dependent variable (Y) used in this study is Return On Equity (ROE). The method used is descriptive statistical analysis method, multiple linear regression analysis, simultaneous test (F test), partial test (t test), and the data is processed using SPSS 25 software. The embodiment, the results of the mudharabah financing t test have no effect on Return On Equity , however, the partial Musyarakah financing (t test) has an effect on Return On Equity, and the simultaneous test of Mudharabah and Musyarakah financing has an effect on Return On Equity of PT Bank Muamalat Indonesia.